Synergetic Effects of Graphene Oxide and Clay on the Microstructure and Properties of HIPS/Graphene Oxide/Clay Nanocomposites. Issue 2 (22nd January 2017) - Rostampour, Amirhosein; Sharif, Mehdi; Mouji, Navid
ABSTRACT: In this paper, double-network structure nanocomposite with improved mechanical and thermal properties were prepared using high-impact polystyrene as a matrix phase, clay and graphene oxide as effective reinforcing fillers through a facile solution intercalation method. The structure and morphology of nanocomposites were characterized by transmission electron microscopy, scanning electron microscopy, X-ray diffraction analysis, and the synergetic effects of clay and graphene oxide on the final properties were investigated using tensile, dynamic mechanical thermal analysis (DMTA) and thermogravimetric analysis (TGA) analysis. Mechanical analysis showed that the combination of graphene oxide and clay exerted a favorable synergistic effect on the tensile modulus and the yield strength of the ternary composite that are greatly improved as compared with neat high-impact polystyrene, high-impact polystyrene/graphene oxide, and high-impact polystyrene/clay binary composites due to the double-network structure formation between the nanofillers as confirmed by the direct morphological observations using transmission electron microscopy and scanning electron microscopy analysis. The viscoelastic behavior showed that storage modulus of ternary composite significantly improvement over than that of the pure matrix, high-impact polystyrene/graphene oxide and high-impact polystyrene/clay while network structure made. TGA and DMTA measurements also demonstrated that thermal stability of high-impact polystyrene matrix modified by graphene oxide and clay slightly enhanced during the creation of dual network structure of graphene oxide and clay. Our data suggest a potential application for the combination of graphene oxide and clay in graphene-based composite materials. GRAPHICAL ABSTRACT: Double-network structure formation and its effect on the improvement of mechanical properties.